Organisasi Mahasiswa: Sudah Tidak Relevan dan Tidak Penting Lagi? - Silalahi, Daniel; Asbari, Masduki; Faliza, Tengku Aisha (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to find out the importance of Student Organizations from different points of view. In this study report, a qualitative descriptive method was used by observing closely because the data source was obtained by listening to oral narratives from the Satu Persen - Indonesian Life School Youtube channel entitled